Impact of Production System on Quality Indices Distribution in Butterhead Lettuce: A Comparative Study among Open Field and Greenhouse - Goñi, María Gabriela (2013)
Butterhead lettuce quality was followed through changes in physical, physiological, microbiological, nutritional and sensory indices during postharvest storage. Production was in greenhouses, traditional and mulch, and in the field. Greenhouse lettuce heads had higher nutritional and sensory quality at harvest and lower enzymatic browning. Increased exposure to environmental conditions for open field grown lettuce heads may initiate defense mechanisms that could affect texture, color and appearance. During refrigerated postharvest storage, greenhouse lettuce heads had better leaf color and texture and were less susceptible to enzymatic browning. There was no difference in postharvest shelf life for greenhouse and field grown plants. Production in greenhouses produced important marketing benefit, along greater weight per plant and leaf number, by increasing producer profitability